Posyandu Jiwa: Accessibility and Acceptability of Persons with Mental Disabilities in Rural Communities - Ramdhani, Fajri Zulia; Astuti, Hastin; Febriyanti, Melinia (The Center for Disability Studies and Services Brawijaya University, 2024)
Despite legal assurances of equal rights and access to healthcare, discrimination and stigma hinder the fulfillment of these rights, impacting employment opportunities and societal integration, particularly for individuals with mental disabilities. The global economic burden of mental health issues underscores the urgency of addressing disparities in access to healthcare services, especially for individuals with mental disabilities. This research is then dedicated to analyzing how accessible to health services for individuals with mental disabilities based on the local integrated services model; and how do rural communities accept individuals with mental disabilities after participating in routine local integrated services, named Posyandu Jiwa in Indonesia, for mental health activities. The research method used is qualitative with a phenomenological approach. We conducted this research in the Inclusive Village program in Gianyar Regency, namely Suwat Village, Sumita Village, Petak Kaja Village, and Singapadu Village.